2010
DOI: 10.1111/j.1439-0507.2008.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivoantifungal activity of essential oils ofCymbopogon martiniandChenopodium ambrosioidesand their synergism against dermatophytes

Abstract: The present study was carried out to evaluate the antifungal efficacy of essential oils (EO) of Cymbopogon martini, Chenopodium ambrosioides and of their combination against dermatophytes and some filamentous fungi in vitro as well as in vivo using a guinea pig model. The minimum inhibitory concentrations of EOs and of their combination were found between 150 and 500 ppm, while those of known antifungal drugs ranged from 1000 to 5500 ppm. EO ointments were prepared and applied against induced ringworm in guine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…MIC of mixture of oils against T. rubrum was 0.02 μl/ml and M. gypseum was 0.04 μl/ml. Our findings are similar to Prasad et al 13 who found the synergistic antifungal efficacy of essential oils of Cymbopogon martini, Chenopodium ambrosiodies and their combinations against dermatophytes and some filamentous fungi in vitro. Our work also coincides with the findings of Cassella et al 14 studied the antifungal potential of tea tree and lavender essential oils alone and in combinations against T. rubrum and T. mentagrophytes and effective inhibition by mixture of oils than a single oils alone.…”
Section: Discussionsupporting
confidence: 92%
“…MIC of mixture of oils against T. rubrum was 0.02 μl/ml and M. gypseum was 0.04 μl/ml. Our findings are similar to Prasad et al 13 who found the synergistic antifungal efficacy of essential oils of Cymbopogon martini, Chenopodium ambrosiodies and their combinations against dermatophytes and some filamentous fungi in vitro. Our work also coincides with the findings of Cassella et al 14 studied the antifungal potential of tea tree and lavender essential oils alone and in combinations against T. rubrum and T. mentagrophytes and effective inhibition by mixture of oils than a single oils alone.…”
Section: Discussionsupporting
confidence: 92%
“…Studies report that the essential oil obtained from this species has antihelmintic activity (particularly against Ascaris lumbricoides), antifungal activity (Prasad, Shukla, Kumar, & Dubey, 2010), activity against Leishmanial (Monzote, García, Montalvo, Linares & Scull, 2009;Monzote, Nance, García, Scull & Setzer, 2011) and acaricide activity (Chiasson, Bostanian, & Vincent, 2004). In the present study, the essential oil from Chenopodium ambrosioides was extracted to determine the secretory structures and to evaluate the biological potential as an antioxidant and antibacterial agent.…”
Section: Introductionmentioning
confidence: 91%
“…It is worth noting that volatile oils containing CIT, GOL and NOL, have proved promising, and may be incorporated into pharmaceutical preparations, alone or in combination (Prasad et al, 2010;Saddiq and Khayyat, 2010;Zore et al, 2011a;Miron et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%